2011
DOI: 10.1105/tpc.111.091538
|View full text |Cite
|
Sign up to set email alerts
|

AGAMOUSTerminates Floral Stem Cell Maintenance inArabidopsisby Directly RepressingWUSCHELthrough Recruitment of Polycomb Group Proteins

Abstract: Floral stem cells produce a defined number of floral organs before ceasing to be maintained as stem cells. Therefore, floral stem cells offer an ideal model to study the temporal control of stem cell maintenance within a developmental context. AGAMOUS (AG), a MADS domain transcription factor essential for the termination of floral stem cell fate, has long been thought to repress the stem cell maintenance gene WUSCHEL (WUS) indirectly. Here, we uncover a role of Polycomb Group (PcG) genes in the temporally prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
306
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(316 citation statements)
references
References 69 publications
(101 reference statements)
3
306
0
7
Order By: Relevance
“…4D), indicating that a bona fide FM remains functional in sup-1 flowers longer than it does in the wild type. AG is responsible for triggering stem cell termination in wild-type flowers by turning off the expression of WUS (18)(19)(20)(21), and most mutants with a delay or loss of floral stem cell termination have defects in AG expression (4). We thus used the gAG-GFP reporter (22) to compare the expression of AG in wild-type and sup-1 flowers, and AG expression appears unaffected in sup-1 flowers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4D), indicating that a bona fide FM remains functional in sup-1 flowers longer than it does in the wild type. AG is responsible for triggering stem cell termination in wild-type flowers by turning off the expression of WUS (18)(19)(20)(21), and most mutants with a delay or loss of floral stem cell termination have defects in AG expression (4). We thus used the gAG-GFP reporter (22) to compare the expression of AG in wild-type and sup-1 flowers, and AG expression appears unaffected in sup-1 flowers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Within the SAM, WUS is expressed specifically in the stem cell organizing center and acts both independently and complementarily with STM in the maintenance of stem cell activity (Laux et al, 1996;Mayer et al, 1998). During flower development, AG terminates stem cell maintenance by repressing WUS by directly or indirectly recruiting PRC2 and LHP1 (Liu et al, 2011;Sun et al, 2014). Interestingly, AtZRF1a/b are not required for the repression of AG and WUS, because expression levels of both AG and WUS are down-regulated in the atzrf1a atzrf1b mutant.…”
Section: Discussionmentioning
confidence: 99%
“…2). It was shown that AG binds to CArG box sequences in the WUS promoter and recruits a Polycomb group (PcG) complex involved in the stable silencing of gene expression through covalent histone modifications (Liu et al, 2011). As a consequence of this direct regulation, WUS expression declines over time.…”
Section: Control Of Floral Meristem Determinacymentioning
confidence: 99%